Julian von Aeclanum : Studien zu seinem Leben, seinem Werk, seiner Lehre und ihrer Überlieferung - Lössl, Josef. (Vigiliae Christianae, Supplements, 2001)
Julian of Aeclanum )ca. 380-441/55 AD) is one of the most exciting figures of 4th/5th century Latin Christianity. Some of the most influential people in the western Church were among his relatives and friends. As a bishop he became famous for his charity and learning. In 418 AD he was deposed for refusing to endorse the condemnation of Pelagius and Caelestius. In a series of writings, mostly against Augustine, he justified his step and clarified his stance. He also rallied political support, not only in Italy, but also in the east. This book tells the story of his life and discusses questions concerning his literary pursuits, philosophy, biblical exegesis and church political activities. It thus throws light not only on Julian as an individual, but on the history and culture of his age.